Quantifying Anuran Microhabitat Use to Infer the Potential for Parasite Transmission between Invasive Cane Toads and Two Species of Australian Native Frogs - Pizzatto, Lígia (Public Library of Science, 2014)
Parasites that are carried by invasive species can infect native taxa, with devastating consequences. In Australia, invading cane toads (Rhinella marina) carry lungworm parasites (Rhabdias pseudosphaerocephala) that (based on previous laboratory studies) can infect native treefrogs (Litoria caerulea and L. splendida). To assess the potential of parasite transmission from the invader to the native species (and from one infected native frog to another), we used surveys and radiotelemetry to quantify anuran microhabitat use, and proximity to other anurans, in two sites in tropical Australia. Unsurprisingly, treefrogs spent much of their time off the ground (especially by day, and in undisturbed forests) but terrestrial activity was common at night (especially in anthropogenically modified habitats). Microhabitat overlap between cane toads and frogs was generally low, except at night in disturbed areas, whereas overlap between the two frog species was high. The situations of highest overlap, and hence with the greatest danger of parasite transmission, involve aggregations of frogs within crevices by day, and use of open ground by all three anuran species at night. Overall, microhabitat divergence between toads and frogs should reduce, but not eliminate, the transmission of lungworms from invasive toads to vulnerable native frogs.